2013
DOI: 10.4308/hjb.20.2.80
|View full text |Cite
|
Sign up to set email alerts
|

Three Species of Ectoparasite Mites (Acari: Pterygosomatidae) Infested Geckos in Indonesia

Abstract: Limited data is hitherto available on the diversity and dispersal of parasitic mites of geckos in Indonesia. Here, we collected three species of geckos, namely Cosymbotus platyurus, Hemidactylus frenatus, and H. garnotii throughout Indonesia to study the distribution and diversity of its parasitic mites. We conducted detail morphological analysis of the mites using whole mount polyvinyl lactophenol and scanning electron microscope preparation. Three species of ectoparasite mites from genus Geckobia were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…It is within these terraces that erosion and dissolution has produced shelters and caves, including Here Sorot Entapa (HSE), the subject of our excavation. Kisar today has an extremely depauperate terrestrial fauna with only a few species of bats, small rodents, small lizards, and snakes recorded (How et al 1996;Maryanto et al 2005;Monk et al 1997;Prawasti et al 2013;Zug 2010). During the course of our surveys we also identified the presence of at least one shrew species.…”
Section: Kisar Islandmentioning
confidence: 99%
“…It is within these terraces that erosion and dissolution has produced shelters and caves, including Here Sorot Entapa (HSE), the subject of our excavation. Kisar today has an extremely depauperate terrestrial fauna with only a few species of bats, small rodents, small lizards, and snakes recorded (How et al 1996;Maryanto et al 2005;Monk et al 1997;Prawasti et al 2013;Zug 2010). During the course of our surveys we also identified the presence of at least one shrew species.…”
Section: Kisar Islandmentioning
confidence: 99%
“…Rico (Rivera et al, 2003), Peru (Quiroz-Gutiérrez et al, 2015), Estados Unidos da América e Brasil (ANJOS et al, 2008), sendo oriundo do continente Africano, assim como o lagarto H. mabouia (Prawasti;Farajallah;Raffiudin, 2013). Região da cloaca danificada pela infestação dos ácaros circulada em vermelho.…”
Section: Resultsunclassified
“…Américas e, desde então, tem fácil adaptação a este ambiente (Prawasti;Farajallah;Raffiudin, 2013). Devido à adaptabilidade, estes ácaros representam parasita potencial para lagartos endêmicos das espécies Gymnodactylus darwinii (Carvalho, 2007), Mabuya macrorhyncha (Da Rocha, 2000), e para outros lagartos como do gênero Tropidurus (Kato, 2017) que, segundo Carvalho (2007), são repteis que dividem o mesmo ambiente que o H. mabouia, representando um risco ecológico a biodiversidade das espécies nativas.…”
Section: áCaros Do Gênero Geckobia E Os Lagartos H Mabouia Foram Inse...unclassified
“…Several studies have revealed the presence of different species of this African mite in some species of geckos of the genus Phyllodactylus Gray, 1828 (Floch and Abonnenc, 1944; Hoffmann and Morales-Malacara, 1985), Hemidactylus Goldfuss, 1820 (Krantz, 1978; Frenkel and Vargas, 2005; Prawasti et al, 2013), or Tarentola (Girot, 1969; De la Cruz, 1973). Two species of these parasites have been cited for the Tenerife gecko: G. canariensis Zapatero-Ramos et al, 1989 and G. tinerfensis Zapatero-Ramos et al, 1989, whose biological cycles and possible adverse effects on this species are unknown.…”
Section: Introductionmentioning
confidence: 99%